EFFECT OF ADDITION RAMIE AND COCONUT COIR FIBERS WITH DIFFERENT CONCENTRATIONS ON TENSILE STRENGTH OF ACRYLIC DENTURE BASE - Prawesthi, Endang; Eka Putri, Adinda; Asylla, Vilza; Arif Wibowo, Sambodo (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Acrylic denture base material has advantages such as good aesthetics, ease of repair, and affordable price, but this denture has mechanical properties, one of which is low tensile strength so fractures often occur during use. Utilization of natural fibers such as ramie (Boehmeria Nivea) and coconut coir (Coco Nucifera L) can be used as an alternative reinforcement for acrylic denture bases. Purpose: To determine the effect of adding ramie fiber and coconut coir fiber at different concentrations on the tensile strength of the acrylic denture base. Method: This study used a laboratory experimental method with a flat dumbell-shaped specimen with a size of 75 í— 10 í— 3 mm based on ISO 527-1 (2019). The specimens consisted of 42 plates which were divided into 7 groups, namely 6 specimens each group without fiber addition (control), with the addition of ramie fiber 1%, 2%, 3%, and the addition of coconut coir fiber 1%, 2%, 3%. Tensile strength testing using Universal Testing Machine (UTM), data were analyzed by One-way ANOVA test and Post Hoc LSD test. Result: The 3% ramie fiber addition group had the highest tensile strength (76.47 MPa), the 1% coconut coir fiber addition group had the lowest tensile strength (58.91 MPa). There was a significant difference in the results of the control group's tensile strength test and the addition of 3% ramie fiber and 1% coconut coir fiber (p-value < 0.05). Conclusion: The greater the concentration of ramie and coconut fiber additions, the higher the tensile strength value, although the tensile strength value in the coconut fiber addition group was lower than the control group and ramie fiber addition.